Controlled trial of psychiatric nurse therapists in primary care. Issue 6476 (20th April 1985) - Marks, I
Abstract : In a randomised controlled clinical trial neurotic patients (mainly phobic and obsessive-compulsive) did significantly better up to one year follow up after receiving behavioural psychotherapy from a nurse therapist rather than routine treatment from a general practitioner. At the end of the year control patients who had not improved had crossover behavioural treatment from the nurse and then improved. Those who dropped out or refused therapy did not show worthwhile gains. Patients preferred being treated in the primary care setting rather than in hospital. Placing nurse therapists in primary care is not only viable but may save more health care resources than it consumes.